Constructing basic science theoretical curriculum evaluation tool, based on Problem-based strategy (A guide for application). - Vafamehr, Vajiheh; Yousefy, Ali Reza; Changiz, Tahereh; Dadgostarnia, Mohammad (Iranian Journal of Medical Education)
Introduction: A variety of educational strategies appropriate for medical student learning have been introduced. Problem- based learning is a major, complex and widespread strategy in medical education, especially in basic science education. In the SPICES model PBL is presented as continuums (from information oriented learning to problem-based learning). In this study, we developed a questionnaires based on continuums as a tool for curriculum evaluation. Method: This developmental study had 2 phases. The first phase was concept mapping and questionnaire development. This phase was performed as an extensive literature review and consensus building in focus groups of experts. The content and face validity of questionnaires was confirmed. The second phase was pilot study. In this phase, the PBL questionnaire was used for evaluation of biology course. All ICM students that had taken biology course two semesters ago completed questionnaires. We used frequency of item selection for determining location on the continuums. The reliabilities were checked by Cronbach's Alpha. Result: The results showed that biology course located in the traditional end of PBL continuum of all aspects of the course (student role, teacher role, resources, content of tests, grading, time management, physical environment). Discussion: Many medical schools from all over the world have implemented PBL curricula and they have assessed effectiveness of these strategies. But very little is known about the evaluation of curriculum based on this strategy. The present work may be considered as a guide for curriculum evaluation.